2020
DOI: 10.1155/2020/8852182
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Malignant Disease, Dermatofibrosarcoma Protuberans of the Breast: A Retrospective Analysis and Review of Literature

Abstract: Dermatofibrosarcoma protuberans (DFSP) is a rare low-grade fibroblastic mesenchymal tumor derived from the dermis. The aim of this retrospective analysis was to summarize the clinicopathological data from our cases and published cases to offer more evidence for the recognition of dermatofibrosarcoma protuberans (DFSP). A total of 6 breast DFSP patients who had received treatment in our hospital were retrospectively enrolled, and detailed clinicopathological data were gathered for analysis. The median age was 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 58 publications
(73 reference statements)
0
19
0
Order By: Relevance
“…Interestingly for DFSP of the breast, there are no case reports that describe use of MMS for resection, very few case reports that describe reconstruction and its complications following resection, and no studies that compare complications between primary closure and reconstruction [ 8 ]. In addition to primary closure, reconstruction techniques cited in the literature include pedicled latissimus dorsi flap, rotation flap, reverse abdominoplasty, pectoralis flap, and reduction mammoplasty to provide wound coverage and to preserve breast shape [ 25 - 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly for DFSP of the breast, there are no case reports that describe use of MMS for resection, very few case reports that describe reconstruction and its complications following resection, and no studies that compare complications between primary closure and reconstruction [ 8 ]. In addition to primary closure, reconstruction techniques cited in the literature include pedicled latissimus dorsi flap, rotation flap, reverse abdominoplasty, pectoralis flap, and reduction mammoplasty to provide wound coverage and to preserve breast shape [ 25 - 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…An additional challenge is balancing adequate resection for margin control and the aesthetic goals of symmetry, especially with breast lesions. The present literature on DFSP of the breast is scarce, with single institution case series describing 1–6 patients resected by WLE [ 8 ]. Although there are no established guidelines for breast reconstruction following DFSP resection, one case report of reconstruction following WLE recommended delaying reconstruction at least 2 years as it may prevent detection of local recurrence and will result in better aesthetic outcomes [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The patients were operated on with a margin of 2-4 cm and postoperative RT was applied to 2 patients. 17 In the case presented by Salim Al-Rahbi et al, firstly, an excisional biopsy was performed and wide local excision was performed after positive surgical margins. Although negative surgical margins were obtained, postoperative RT was applied to the case.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes are significantly worse when DFSP undergoes fibrosarcomatous (FS) transformation (FS-DFSP), which is associated with an increased risk of metastasis, reduced CD34 staining, and a herringbone pattern with increased atypia and mitoses. 3,4 A systematic review of outcomes for FS-DFSP and DFSP showed that the risk of local recurrence, metastasis, and death from disease in FS-DFSP was significantly higher as compared to DFSP (local recurrence 29.8% vs 13.7%, risk ratio 2.2, 95% confidence interval [CI] 1.7-2.9; metastasis 14.4% vs 1.1%, risk ratio 5.5, 95% CI 4.3-7.0; and death from disease 14.7% vs 0.8%, risk ratio 6.2, 95% CI 5.0-7.8). 4 In the United States, the overall annual incidence of DFSP was 4.1 persons per million person-years in 2000 to 2010.…”
Section: Introductionmentioning
confidence: 99%